Articular inflammation induced by an enzymatically-inactive Lys49 phospholipase A2: activation of endogenous phospholipases contributes to the pronociceptive effect - Dias,Renata Gonçalves (2017)
Abstract Background Arthritis is a set of inflammatory conditions that induce aching, stiffness, swelling, pain and may cause functional disability with severe consequences to the patient’s lives. These are multi-mediated pathologies that cannot be effectively protected and/or treated. Therefore, the aim of this study was to establish a new model of acute arthritis, using a Lys49-PLA2 (Bothrops asper myotoxin II; MT-II) to induce articular inflammation. Methods The articular inflammation was induced by MT-II (10 μg/joint) injection into the left tibio-tarsal or femoral-tibial-patellar joints. Cellular influx was evaluated counting total and differential cells that migrated to the joint. The plasma extravasation was determined using Evans blue dye. The edematogenic response was evaluated measuring the joint thickness using a caliper. The articular hypernociception was determined by a dorsal flexion of the tibio-tarsal joint using an electronic pressure-meter test. The mediators involved in the articular hypernociception were evaluated using receptor antagonists and enzymatic inhibitors. Results Plasma extravasation in the knee joints was observed 5 and 15 min after MT-II (10 μg/joint) injection. MT-II also induced a polymorphonuclear cell influx into the femoral-tibial-patellar joints observed 8 h after its injection, a period that coincided with the peak of the hyperalgesic effect. Hyperalgesia was inhibited by the pretreatment of the animals with cyclooxygenase inhibitor indomethacin, with type-2 cyclooxygenase inhibitor celecoxib, with AACOCF3 and PACOCF3, inhibitors of cytosolic and Ca2+-independent PLA2s, respectively, with bradykinin B2 receptor antagonist HOE 140, with antibodies against TNFα, IL-1β, IL-6 and CINC-1 and with selective ET-A (BQ-123) and ET-B (BQ-788) endothelin receptors antagonists. The MT-II-induced hyperalgesia was not altered by the lipoxygenase inhibitor zileuton, by the bradykinin B1 receptor antagonist Lys-(Des-Arg9,Leu8)-bradykinin, by the histamine and serotonin antagonists promethazine and methysergide, respectively, by the nitric oxide inhibitor LNMMA and by the inhibitor of matrix 1-, 2-, 3-, 8- and 9- metalloproteinases GM6001 (Ilomastat). Conclusion These results demonstrated the multi-mediated characteristic of the articular inflammation induced by MT-II, which demonstrates its relevance as a model for arthritis mechanisms and treatment evaluation.